Reduced etiological role for enteropathogenic Escherichia coli in cases of diarrhea in Brazilian infants - Rodrigues, J.; Thomazini, C. M.; Morelli, A.; de Batista, GCM (Amer Soc Microbiology, 2004)
Previously common in Brazil, enteropathogenic Escherichia coli (EPEC) strains of serogroups O55, O111, and O119 are now rare, while enteroadherent strains other than EPEC, belonging to serogroups such as O125, were prevalent among 126 diarrheic infants less than 1 year old who were surveyed. None of these strains had the EPEC bundle-forming pilus (bkA) gene.